Biaya Transaksi Usaha Penangkapan Ikan di Kota Pekalongan - Eva Anggraini (Institut Pertanian Bogor, 2007)
Economic efficiency is often measured from production aspect and lack of attention to non-production aspect, such as transaction cost.